Skill-Based Approach Applied to Gifted Students, its Potential in Latin America - Almazán-Anaya, Andrew Alexi; Lozano-Rodríguez, Armando (Revista Electrónica Educare, 2015)
This paper presents, as a reflective essay, the current educational situation of gifted students (with more intelligence than the average) in Latin America and the possibility of using skill-based education within differentiated programs (intended for gifted individuals), a sector where scarce scientific studies have been done and a consensus of an ideal educative model has not been reached yet. Currently these students, in general, lack of specialized educational assistance intended to identify and develop their cognitive abilities, so it is estimated that a high percentage (95%) of such population is not detected in the traditional education system. Although there are differentiated education models, they are rarely applied. A student-centered education program is a solution proposed to apply this pedagogical model and cover such population. The characteristics of this program that do support differentiated instruction for gifted individuals compatible with experiences in the US, Europe and Latin America are analyzed. Finally, this paper concludes with an analysis of possible research areas that, if explored in the future, would help us to find answers about the feasibility and relation between skill-based programs and differentiated education for gifted students.